Трансформація клієнтського досвіду через впровадження інтерактивних та електронних меню в закладах ресторанного господарства - Круль, Галина Ярославівна; Заячук, Оксана Григорівна; Смик, Оксана Степанівна (Тернопіль: ФОП Осадца Ю.В., 2026)
Introduction. The modern hospitality industry is undergoing a profound digital transformation, in which electronic menus have evolved from supplementary service features into strategic tools for managing the customer experience. In the context of post-pandemic recovery and the challenges associated with the imposition of martial law in Ukraine, the digitization of service processes in food service establishments is becoming crucial. The implementation of interactive systems (QR codes, tablet menus, mobile apps) is not only a tool for improving operational efficiency but also a means of ensuring safety, inclusivity, and a barrier-free service environment. The relevance of this study stems from the need to bridge the “digital divide” between generations of consumers and to find the optimal balance between automation and preserving the emotional aspect of traditional hospitality. The primary purpose of this study is to conduct an in-depth, multidimensional analysis of how the implementation of interactive and electronic menus is changing the customer experience in the restaurant industry. This study aims to assess the current level of consumer adaptation to various digital interfaces, identify psychological and functional barriers to technology adoption, and determine specific factors that contribute to customer loyalty in a digital service environment. Furthermore, the article aims to establish a scientifically grounded foundation for achieving an optimal balance between automated efficiency and personalized “High Touch” hospitality service, which remains the hallmark of the industry. Methods. To achieve the goal, a systematic approach and a complex of scientific methods were used. The theoretical basis of the study was formed through the analysis of domestic and foreign scientific literature on digitalization in the restaurant business. The empirical part of the study is based on a sociological survey (questionnaire) of consumers of restaurant services. The survey focused on identifying patterns of using QR menus, assessing awareness of specialized aggregator services (such as Expirenza), and determining the influence of innovations on the choice of a catering establishment. The study utilized statistical analysis to differentiate responses by age categories and identify "digital gap" barriers. Results. The study revealed a high level of consumer readiness for basic digital solutions: 83% of respondents have experience using QR menus. However, a significant gap was identified between general technological readiness and awareness of specialized service platforms; for instance, 77.7% of respondents are unfamiliar with the Expirenza service. The analysis confirmed the existence of a "digital divide," where consumers aged 41-55 and older remain the least adapted to self-order systems and prefer traditional analog media. It was established that for over 55% of consumers, the innovativeness of the establishment is a significant factor in their choice. The key determinants of loyalty in the digital service process were identified as the speed of logistic processes (30%) and the ergonomics of the menu interface (27.9%). Findings suggest that digital interfaces minimize communicative pressure and provide psychological comfort, especially for younger demographics. Conclusions. The research concludes that digital technologies in the restaurant business should be viewed not as a replacement for traditional service, but as a powerful additional competitive advantage. The optimal model for modern establishments is a hybrid approach (High Tech + High Touch), which integrates the advantages of artificial intelligence and interactive systems while maintaining the facilitating role of staff to support the authentic atmosphere of hospitality. The practical significance of the results lies in the possibility of their use by management to optimize operational processes and create an inclusive service environment. Future research should focus on the impact of AI-driven predictive personalization on long-term customer relationships.
Transformation of customer experience through the implementation of interactive and electronic menus in the restaurant industry
Keywords: ресторанне господарство; електронне меню; QR-технології; споживчий досвід; цифрова трансформація; лояльність; інклюзивність